Long-term prognostic implications of brachial-ankle pulse wave velocity in patients undergoing percutaneous coronary intervention - Kim, Byung Sik; Ahn, Jong-Hwa; Shin, Jeong-Hun; Kang, Min Gyu; Kim, Kye-Hwan; Bae, Jae Seok; Cho, Yun Ho; Koh, Jin-Sin; Park, Yongwhi; Hwang, Seok-Jae; Tantry, Udaya S.; Gurbel, Paul A.; et al. (Frontiers in Medicine, 2024)
Objective: The long-term clinical effect of arterial stiffness in high-risk disease entities remains unclear. The prognostic implications of brachial-ankle pulse wave velocity (baPWV) were assessed using a real-world registry that included patients who underwent percutaneous coronary intervention (PCI). Methods: Arterial stiffness was measured using baPWV before discharge. The primary outcome was net adverse clinical events (NACE), defined as a composite of all-cause death, non-fatal myocardial infarction, non-fatal stroke, or major bleeding. Secondary outcomes included major adverse cardiac and cerebrovascular events (MACCE: a composite of all-cause death, non-fatal myocardial infarction, or non-fatal stroke), and major bleeding. The outcomes were assessed over a 4-year period. Results: Patients (n=3,930) were stratified into high- and low-baPWV groups based on a baPWV cut-off of 1891 cm/s determined through time-dependent receiver operating characteristic curve analysis. baPWV was linearly correlated with 4-year post-PCI clinical events. The high baPWV group had a greater cumulative incidence of NACE, MACCE, and major bleeding. According to multivariable analysis, the high baPWV groups had a significantly greater risk of 4-year NACE (adjusted hazard ratio [HRadj]: 1.44; 95% confidence interval [CI]: 1.12–1.85; p=0.004), MACCE (HRadj: 1.40; 95% CI: 1.07–1.83; p=0.015), and major bleeding (HRadj: 1.94; 95% CI: 1.15–3.25; p=0.012). Conclusions: In PCI-treated patients, baPWV was significantly associated with long-term clinical outcomes, including ischemic and bleeding events, indicating its value for identifying high-risk phenotypes.